The Legal Protection for Notary Employees who are Instrumental Witnesses in Notary Deed - Edi Suarto; Gunarto Gunarto; Arpangi Arpangi; Aryani Witasari (Sultan Agung Notary Law Review, 2022)
This research aims to identify and analyze legal protection for Notary employees who are instrumental witnesses in the Notary Deed, and to identify and analyze legal responsibilities for Notary employees who are instrumental witnesses in the Notary Deed which contains defects. This study used a normative juridical approach by using descriptive analytical research specifications. The type of data in this legal research was normative using primary legal materials and secondary legal materials, as well as tertiary legal materials. The data collection method in this study was in the form of literature and the data analysis method used qualitative data analysis. Based on the results of research and discussion, that the legal protection of a Notary employee who is an instrumenter witness is found in Act No. 31 of 2014 concerning Amendments to Act No. 13 of 2006 concerning the Protection of Witnesses and Victims. Then that the Notary employee who is the instrumenter witness in the Notary deed is not responsible for the deed and if there is a formal defect in the Notary Deed so that the Notary Deed is degraded its proof value as an underhand deed or if in the Notary Deed there is a material defect so that the Notary Deed can be canceled or null and void by law is not the responsibility of the Notary employee who is the instrumenter witness in the deed.